Effectiveness of home-based cardiac rehabilitation programs on health outcomes of persons with heart failure: An umbrella review - Promwong, Waiyaporn; Meenongwah, Jaroonsree; Kenbubpha, Kedsaraporn; Suyasa, I Gede Putu Darma (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Home-based cardiac rehabilitation (HBCR) serves as a crucial alternative to center-based cardiac rehabilitation (CBCR) for patients with heart failure (HF), aiming to enhance access and adherence. However, evidence of its effectiveness is dispersed across numerous systematic reviews with varying findings, necessitating a high-level synthesis to clarify HBCR’s overall impact. Objective: To synthesize and critically evaluate evidence from systematic reviews and meta-analyses on the effectiveness of home-based cardiac rehabilitation in improving health outcomes among patients with heart failure. Design: An umbrella review of systematic reviews and meta-analyses Data Sources: A systematic search was conducted in the Cochrane Library, JBI Evidence Synthesis, PubMed, Medline, CINAHL, Epistemonikos, and ThaiJo databases for studies in English or Thai up to April 11, 2025. Review Methods: The review adhered to JBI and PRISMA guidelines. Outcomes included functional capacity, quality of life (QOL), mortality, hospital readmissions, and adverse events. Study quality was assessed using the JBI checklist. Results: Fifteen systematic reviews and meta-analyses met the inclusion criteria, all of which were of high methodological quality. The evidence consistently demonstrates that HBCR significantly enhances functional capacity compared to usual care, with outcomes comparable to those of CBCR. However, findings for other outcomes were inconsistent; HBCR’s impact on QOL and left ventricular ejection fraction (LVEF) varied due to program content and methodological heterogeneity, and it did not significantly reduce mortality or hospital readmissions compared to usual care or CBCR. No significant differences in adverse events were observed between HBCR, CBCR, and usual care. Conclusion: HBCR is a safe and effective intervention for improving functional capacity in patients with heart failure, offering a viable alternative to CBCR. However, its effects on quality of life, hospital readmissions, and mortality remain inconsistent. These findings highlight HBCR’s potential role in expanding access, though further research is needed to optimize program design. Registry: PROSPERO (CRD42023484051)